Geopolitical risk and China's oil security. (April 2022) - Gong, Xu; Sun, Yi; Du, Zhili
Abstract: This paper aims to make a comprehensive evaluation of China's oil situation from 2000 to 2018. We establish an evaluation framework from three dimensions of oil supply, oil consumption and oil ecology, and calculate the comprehensive score and scores of three dimensions. Results show that the comprehensive score of China's oil security increased from 0.3 to about 0.6 in 2000–2018. After rapid growth from 2003 to 2008, the oil supply security score stabilized at the level of 0.6. In general, China's oil security situation is steadily improving. Further, ADL-MIDAS model is employed to investigate the impact of four types of geopolitical risks (GPRs) on China's oil security. The findings suggest that GPRs have negative effects on China's comprehensive oil security. In the robustness tests, these effects don't change with adjustments to the assessment framework, changes in subjective weights, or the choice of regression models. The impacts of GPRs on China's oil security are mainly realized through the oil supply dimension. GPRs threatening China's oil security are reflected in oil interruption in the international market. Finally, the paper puts forward several policy implications from the perspective of oil security assessment and GPRs. Highlights: The paper evaluates and calculates the scores of China's oil security. The paper uses the ADL-MIADS model to study the relationship between geopolitical risks and oil security. The study discovers that the overall trend of China's oil security is rising. Geopolitical risks have negative impacts on China's oil security. Negative impacts mainly come from oil-exporting countries.